1994
DOI: 10.2307/1941602
|View full text |Cite
|
Sign up to set email alerts
|

Intratree Variation in Foliage Development Influences the Foraging Strategy of a Caterpillar

Abstract: Zeiraphera canadensis Mut. & Free. (Lepidoptera: Tortricidae) is an early season folivore that feeds exclusively on young foliage of white spruce (Picea glauca (Moench) Voss). Most first-instar larvae are unable to colonize vigorous upper-crown apical buds due to the limited time during which newly burst buds are suitable to young larvae and the distinct acropetal bud development pattern exhibited by white spruce. However, late second-and early third-instar larvae abandon buds from the lower and middle crown a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 46 publications
2
43
0
Order By: Relevance
“…Population growth is thus five times higher if larvae hatch in synchrony with host bud burst (Cockfield and Mahr 1993). First-instar Zeiraphera canadensis show dramatically lower survivorship (from 50%-70% to less than 25%) when fed on 4-5 day old white spruce (Picea glauca (Moench) Voss) foliage; in the field, these larvae move in the tree, tracking changes in foliar quality following bud burst away from the most vigorous apical shoots to those with more immature foliage (Carroll and Quiring 1994).…”
Section: Phenological Relationships Under a Changing Climatementioning
confidence: 99%
“…Population growth is thus five times higher if larvae hatch in synchrony with host bud burst (Cockfield and Mahr 1993). First-instar Zeiraphera canadensis show dramatically lower survivorship (from 50%-70% to less than 25%) when fed on 4-5 day old white spruce (Picea glauca (Moench) Voss) foliage; in the field, these larvae move in the tree, tracking changes in foliar quality following bud burst away from the most vigorous apical shoots to those with more immature foliage (Carroll and Quiring 1994).…”
Section: Phenological Relationships Under a Changing Climatementioning
confidence: 99%
“…Lack of impacts on early instar survival associated with the density of young larvae suggests that intraspecific competition is not important to young larvae. Indeed, Carroll and Quiring (1994) found that even at very high densities, intraspecific competition does not occur among Z. canadensis larvae until they become third and fourth instars.…”
Section: Discussionmentioning
confidence: 99%
“…For early season folivores, synchrony between the presence of feeding stages and the occurrence of young foliage is critical to survival (Raupp et al 1988;Hunter and Lechowicz 1992;Quiring 1992;Lawrence et al 1997;Carroll 1999). Indeed, the constraints associated with synchrony between egg hatch and bud burst have been shown to be significant forces shaping larval foraging strategies (Carroll and Quiring 1994;Carroll 1999). Consequently, herbivory-induced shifts in the phenology of host plants during the subsequent growing season could have significant impacts on the abundance and distribution of insect herbivores (Quiring and McKinnon 1999).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations